Sediment echosounder raw data (Innomar SES-2000 entire dataset) of HSV FISÁLIA cruise in 2020, Southwest Algarve shelf, North Atlantic Ocean - Pedro J M Costa; Lisa Feist (PANGAEA, 2024)
This dataset contains raw sub-bottom profiles from the southwestern Algarve shelf, Portugal. The profiles were recorded in January 2020 during a campaign onboard HSV FISÁLIA of the Portuguese Navy for project OnOff "Coupling onshore and offshore tsunami record: complementary tools for a broader perspective on tsunami events", funded by FCT (Portuguese Foundation for Science and Technology) grant PTDC/CTAGEO/28941/2017. The dataset compiles all sub-bottom profiles recorded with an Innomar SES-2000 quattro system. This system consists of four individual transducers functioning as seismic sources and receivers. It was used in single-beam mode with a sampling frequency of 8 kHz. The shot interval during the survey was not set to a specific value but automatically optimized by the system as a function of the water depth. As a result, the ping rate changed slightly around 7-8 pings/s. The theoretical vertical resolution was around 5 cm. The dataset contains raw data as .txt (with coordinates), .PRM, .raw and .sgy.